Effect of Calcium and Magnesium Ions In Microbial Cells adhesion of Attached Growth Systems for the Enhancement Of Biohydrogen Production - Yiek,Wee Kiong (School of Environmental Engineering, University Malaysia Perlis, 2016)
To examine the influence of calcium and magnesium ions in attached growth systems for the enhancement of biohydrogen production. To investigate the suitable concentration of calcium and magnesium ions added in attached growth systems to optimum the production of hydrogen. To investigate the amount of hydrogen gas produce from different concentration of calcium and magnesium through dark fermentative hydrogen production.